Effects of isoflavones (soy phyto-estrogens) on serum lipids: a meta-analysis of randomized controlled trials - Yeung, John (BioMed Central, 2003)
OBJECTIVES: To determine the effects of isoflavones (soy phyto-estrogens) on serum total cholesterol (TC), low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride (TG). METHODS: We searched electronic databases and included randomized trials with isoflavones interventions in the forms of tablets, isolated soy protein or soy diets. Review Manager 4.2 was used to calculate the pooled risk differences with fixed effects model. RESULTS: Seventeen studies (21 comparisons) with 853 subjects were included in this meta-analysis. Isoflavones tablets had insignificant effects on serum TC, 0.01 mmol/L (95% CI: -0.17 to 0.18, heterogeneity p = 1.0); LDL, 0.00 mmol/L (95% CI: -0.14 to 0.15, heterogeneity p = 0.9); HDL, 0.01 mmol/L (95% CI: -0.05 to 0.06, heterogeneity p = 1.0); and triglyceride, 0.03 mmol/L (95% CI: -0.06 to 0.12, heterogeneity p = 0.9). Isoflavones interventions in the forms of isolated soy protein (ISP), soy diets or soy protein capsule were heterogeneous to combine. CONCLUSIONS: Isoflavones tablets, isolated or mixtures with up to 150 mg per day, seemed to have no overall statistical and clinical benefits on serum lipids. Isoflavones interventions in the forms of soy proteins may need further investigations to resolve whether synergistic effects are necessary with other soy components.